Electrode, method for producing the same, battery, and method for producing the same
By dispersing conductive additives within and on the surface of electrode granules, the issues of high resistance and performance degradation in battery electrodes are addressed, resulting in electrodes with low volume resistance and enhanced cycle stability.
Patent Information
- Application Number
- JP2023102056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Existing electrode manufacturing methods for batteries, particularly those using granules, face issues with high resistance and deteriorating battery performance due to conductive agent aggregation and broken conductive paths during charge/discharge cycles.
The electrodes are designed with granules containing active material particles and a conductive additive that is dispersed within and attached to the surface without agglomeration, with specific size and composition controls to maintain conductivity.
This approach results in electrodes with low volume resistance and improved cycle characteristics, maintaining battery performance over repeated charge/discharge cycles.
Smart Images

Figure 2025002118000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode, a method for manufacturing an electrode, a battery, and a method for manufacturing a battery. [Background technology]
[0002] There are many methods for producing electrodes for use in batteries such as lithium ion batteries by adhering an active material onto a current collector to form an electrode. These methods can be broadly divided into wet methods and dry methods from the viewpoint of whether or not an electrode precursor containing an active material is made into a slurry. In the wet method, an active material, a polymer, a solvent, etc. are mixed to obtain a slurry, and the obtained slurry is applied onto a current collector and dried to form an electrode. On the other hand, in the dry method, an electrode is formed without going through a step of forming a slurry of a solvent and an active material. For example, a granule containing an active material is formed in advance, and this is transferred to a current collector to form an electrode.
[0003] Patent Document 1 discloses a technique for forming granules containing an active material in advance and transferring the granules onto a current collector. Patent Document 1 discloses a method for producing an electrode sheet, including a granulation step for obtaining wet granules containing active material particles, a binder, and a solvent, a molding step for obtaining a compact by molding an aggregate of the granules obtained in the granulation step into a planar or block-like shape, and a step for forming the compact obtained in the molding step into a film and transferring the film to a current collector. Patent Document 2 discloses a technique for spray granulation using a slurry in which positive electrode active material particles and fibrous carbon are sufficiently dispersed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-201318 A [Patent Document 2] JP 2009-176721 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the field of batteries such as lithium ion batteries, it is desired that not only the initial electrical characteristics of the battery but also the battery performance does not deteriorate even after repeated charge and discharge cycles. However, when the active material layer is transferred to the current collector foil using the granules disclosed in Patent Document 1, the resistance of the electrode increases and the battery tends to not perform sufficiently. In the case of the granules disclosed in Patent Document 2, the battery performance may deteriorate after repeated charge and discharge cycles. In addition, when forming an electrode using granules, it is sometimes desired to increase the amount of conductive assistant in order to strengthen the conductive network between the particles, but if a large amount of fibrous conductive assistant is used, the conductive assistant aggregates and the desired characteristics cannot be obtained. On the other hand, repeated charge and discharge with a small amount of conductive assistant may break the path between the conductive assistant and the active material due to the expansion and contraction of the active material.
[0006] As a result of investigations, the present inventors have found that when an electrode is formed using a granule containing an active material, a battery having good characteristics can be obtained by optimizing the aggregation state of the conductive assistant present on the surface and inside of the granule.
[0007] The present invention has been made in view of the above circumstances, and provides an electrode which has low volume resistivity and can provide good cycle characteristics when applied to a battery. [Means for solving the problem]
[0008] That is, according to the present invention, there are provided an electrode, a method for manufacturing an electrode, a battery, and a method for manufacturing a battery, as described below. 1. An electrode comprising a granule, The granules contain active material particles and a conductive assistant, The electrode, wherein the conductive assistant adheres to the surfaces of the active material particles in a dispersed state without agglomerating into lumps, and the conductive assistant is present inside the granules. 2. The electrode according to 1., wherein the average particle size of the granules calculated from a scanning electron microscope photograph is 15 μm or more and 80 μm or less. 3. The electrode according to 1. or 2., wherein the active material particles have an average particle size of 1.0 μm or more and 10.0 μm or less. 4. The electrode according to any one of 1. to 3., wherein the conductive assistant comprises at least one selected from the group consisting of carbon black, carbon nanofibers, and carbon nanotubes. 5. The electrode according to any one of 1. to 4, wherein the granules further contain a solid electrolyte. 6. A method for producing an electrode according to any one of 1. to 5., a step of spraying a dispersion liquid in which the conductive assistant is dispersed onto the active material particles while mixing and stirring the active material particles to form the granules; placing the granules on a current collector and pressing them; A method for producing an electrode comprising the steps of: 7. A method for producing the electrode according to 6., comprising the steps of: a step of mixing and stirring the active material particles and the solid electrolyte, while spraying and adding the dispersion liquid in which the conductive assistant is dispersed to the active material particles to form the granules; (A) placing the granules on a surface of a current collector or on a surface layer formed on the surface of a current collector and pressing the granules; or (B) placing the granules on a surface of a release film, pressing the granules, peeling them off from the release film, and placing the granules on a solid electrolyte layer; A method for producing an electrode comprising the steps of: 8. A battery comprising the electrode described in any one of 1. to 5. 9. The battery according to claim 8, The battery further includes an electrolyte layer. 10. A method for manufacturing a battery, comprising the method for manufacturing an electrode according to 6. or 7. Effect of the Invention
[0009] According to the present invention, it is possible to provide an electrode which has a low volume resistivity and can provide good cycle characteristics when applied to a battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described.
[0011] <Electrode> The electrode according to this embodiment is an electrode including a granule, the granule containing active material particles and a conductive assistant, the conductive assistant adhered to the surface of the active material particles in a dispersed state without agglomerating into clumps, and the conductive assistant present inside the granule.
[0012] As a result of extensive research, the present inventors have found that when an electrode is formed using a granule containing an active material, the volume resistance of a battery cell and an increase in resistance after repeated charge / discharge cycles can be suppressed by appropriately arranging a conductive assistant on the surface and internal structure of the granule, specifically, between the active material particles.
[0013] More specifically, it is presumed that the conductive assistant adheres in a dispersed state without agglomerating into lumps and penetrates into the electrode granules, thereby improving the conductive path between the active materials, and the conductive path is maintained without being broken even when Li ions are repeatedly inserted and removed through repeated charge and discharge cycles.
[0014] The average particle size of the granules is preferably 15 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more, and is preferably 80 μm or less, more preferably 70 μm or less, and even more preferably 60 μm or less. In the present invention, the average particle size of the granules means the particle size at an integrated value of 50% (median size: D50) in the particle size distribution (volume basis) measured by a laser diffraction scattering method.
[0015] The average particle size of the active material particles is preferably 1.0 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more, from the viewpoint of optimal adhesion of the conductive assistant to the active material surface. It is preferably 10.0 μm or less, more preferably 5.0 μm or less, and even more preferably 4.0 μm or less. In the present invention, the average particle size of the active material particles means the particle size at 50% of the integrated value (median size: D50) in the particle size distribution (volume basis) measured by a laser diffraction scattering method. The type of the active material is not particularly limited, and may be a positive electrode active material or a negative electrode active material.
[0016] When the active material is a positive electrode active material, the active material may be, for example, a composite oxide of lithium and a transition metal, such as a lithium-nickel composite oxide, a lithium-cobalt composite oxide, a lithium-manganese composite oxide, a lithium-nickel-manganese composite oxide, a lithium-nickel-cobalt composite oxide, a lithium-nickel-aluminum composite oxide, a lithium-nickel-cobalt-aluminum composite oxide, a lithium-nickel-manganese-cobalt composite oxide, a lithium-nickel-manganese-aluminum composite oxide, or a lithium-nickel-cobalt-manganese-aluminum composite oxide; a transition metal sulfide, such as TiS2, FeS, or MoS2; MnO, VO5, or VO 13 , transition metal oxides such as TiO2, and olivine-type lithium phosphate. The olivine-type lithium phosphate contains, for example, one or more elements selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, lithium, phosphorus, and oxygen. These compounds may have some elements partially substituted with other elements in order to improve their properties.
[0017] Among the compounds listed above, the positive electrode active material preferably contains one or more selected from the group consisting of olivine-type lithium iron phosphate, lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide. These positive electrode active materials have a high working potential, a large capacity, and a large energy density.
[0018] When the active material is a negative electrode active material, the negative electrode active material includes a carbon-based active material, which is preferably natural graphite, artificial graphite, hard carbon, soft carbon, or any mixture thereof. Here, graphite is a carbon material having hexagonal plate-like crystals of a hexagonal system, and is sometimes called graphite, etc. Natural graphite and artificial graphite include natural graphite coated with amorphous carbon and artificial graphite coated with amorphous carbon. Here, the term "amorphous carbon" refers to a carbon material that is amorphous as a whole and has a random network structure of microcrystals, which may partially have a structure similar to that of graphite. Examples of amorphous carbon include carbon black, coke, activated carbon, carbon fiber, carbon nanotubes, hard carbon, soft carbon, and mesoporous carbon. When using artificial graphite, the interlayer distance d value (d 002 ) is preferably 0.33 nm or more. The crystal structure of artificial graphite is generally thinner than that of natural graphite. When artificial graphite is used as a negative electrode active material for non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, it is necessary that the artificial graphite has an interlayer distance that allows lithium ions to be inserted. The interlayer distance that allows lithium ions to be inserted and removed is called the d value (d 002) and if the d value is 0.33 nm or more, lithium ions can be inserted and removed without any problems. The negative electrode active material may contain a silicon-based active material (A) containing SiOx (wherein x is a number satisfying 0.5≦x≦1.6), and a carbon-based active material.
[0019] When the entire granule according to this embodiment is taken as 100 parts by mass, the content of the active material is preferably 95.0 parts by mass or more, more preferably 96 parts by mass or more, even more preferably 97 parts by mass or more, and preferably 99.5 parts by mass or less, more preferably 99.0 parts by mass or less, even more preferably 98.5 parts by mass or less.
[0020] The conductive assistant preferably contains at least one selected from the group consisting of carbon black, carbon nanofibers, and carbon nanotubes. The carbon black used as the conductive assistant preferably has an aggregate structure in which carbon particles having a nanoparticle size are linked together in a beaded shape. As the carbon black, acetylene black, ketjen black, etc. can be used. Also, as the conductive assistant, carbon nanotubes formed of a substance composed of carbon atoms such as graphene into a cylindrical shape with a diameter of several nm and a length of several mm can be used. In particular, bundled single-walled carbon nanotubes formed of a substantially single layer around the cylinder, or multi-walled carbon nanotubes formed of multiple layers around the cylinder can be used.
[0021] When the entire granule of this embodiment is taken as 100 parts by mass, the content of the conductive assistant is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.5 parts by mass or less.
[0022] The granules of the electrode according to this embodiment further contain a polymer, and it is preferable that the polymer is present on the surface of the active material particles, and that the polymer is present on the surface and inside of the granules.
[0023] The polymer may be, for example, polyvinylidene fluoride (PVdF), polyvinylpyrrolidone (PVP), polytetrafluoroethylene, polyimide, polyamideimide, polyamide, etc., or may contain two or more of these, but is not limited thereto as long as it can exist stably even in the presence of an organic solvent.
[0024] When the total amount of the granules according to this embodiment is 100 parts by mass, the content of the polymer is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less.
[0025] The granules according to this embodiment may further contain a solid electrolyte.
[0026] The type of solid electrolyte is not particularly limited, and may be selected from, for example, sulfide-based amorphous solid electrolytes, oxide-based amorphous solid electrolytes, oxide-based crystalline solid electrolytes, sulfide-based crystalline solid electrolytes, glass ceramics, thio-LiSiO-based crystals, argyrodite-type crystal structures, and combinations thereof. From the viewpoints of lithium ion conductivity and electrochemical stability, argyrodite-type sulfide solid electrolytes are preferred.
[0027] The method for manufacturing an electrode according to this embodiment includes the steps of: forming the granules by spraying a dispersion liquid in which the conductive assistant is dispersed onto the active material particles while mixing and stirring the active material particles; and placing the granules on a current collector and pressing the current collector. The method for forming the granules is not particularly limited, and examples thereof include stirring granulation, fluidized bed granulation, rolling granulation, extrusion granulation, spray granulation, compression granulation, etc. These granulation methods may be arbitrarily selected or combined.
[0028] A dispersion containing a conductive assistant and a polymer that have been highly dispersed in advance is attached to active material particles without containing any other organic solvent, to prepare an active material with a uniform conductive assistant formed on the surface. The particle size varies depending on the equipment used to mix and stir these materials, but it is possible to control it by the amount and timing of spraying the dispersion of the conductive assistant and polymer, as well as the mixing and stirring times. In addition, it is possible to obtain granules with any particle size distribution by classifying the granules through a sieve.
[0029] The electrode according to this embodiment may further include an electrolyte layer, which may be in the form of a polyolefin separator containing an electrolytic solution, or a solid electrolyte not containing an electrolytic solution.
[0030] It goes without saying that the electrode according to this embodiment may include a current collector in addition to the granules. The material of the current collector is not particularly limited, but when the current collector is a positive electrode current collector, aluminum foil is preferable. When the current collector is a negative electrode current collector, the material is selected from the group consisting of copper, stainless steel, nickel, titanium, or an alloy thereof, and copper is particularly preferable. The shape of the current collector layer is not particularly limited, and may be a foil, a flat plate, or a mesh. For example, the thickness is 0.001 mm or more and 0.5 mm or less.
[0031] The method for producing an electrode according to this embodiment preferably includes the steps of: mixing and stirring the active material particles and the solid electrolyte, while spraying and adding the dispersion liquid in which the conductive assistant is dispersed onto the active material particles to form the granules; and (A) placing the granules on a surface of a current collector or on a surface layer formed on the surface of a current collector and pressing the granules, or (B) placing the granules on the surface of a release film, pressing the granules, peeling them off from the release film, and placing them on a solid electrolyte layer.
[0032] When the solid electrolyte is contained in the granules, it is preferable that the dispersion of the conductive assistant, which is prepared separately from the active material particles and in which the conductive assistant and the polymer are highly dispersed in a solvent, contains almost no water. For example, a solvent that has a water content of 0.001% or less and can dissolve the binder is suitable. One example is dehydrated xylene, but is not limited to this.
[0033] When the solid electrolyte is contained in the granules, the granulation step and / or the pressing step are preferably carried out in an environment with a dew point of -40°C and a moisture concentration of 127 ppm.
[0034] (A) In the case where the step of disposing the granules on the surface of a current collector or on a surface layer formed on the surface of a current collector and pressing is included, the pressing method is not particularly limited as long as it is possible to form electrode granules containing an electrode active material on the current collector, but a roll-type pressure molding method is preferred. In the roll-type pressure molding method, a long current collector is wound in a roll shape and is arranged so that the current collector passes between a pair of rolls while being unwound and wound up. The granules are supplied onto the current collector before passing through the rolls, and are compressed when passing between the rolls to form an electrode sheet. In order to adjust the supply amount of the granules, it is preferable to supply the thickness while smoothing the surface with a squeegee or the like before being supplied between the rolls. The current collector foil may be formed with a surface layer containing a polymer to enhance the binding property with the granules.
[0035] (B) In the case where the process includes a step of placing the granules on the surface of a release film, pressing the granules, peeling them off from the release film, and placing the granules on a solid electrolyte layer, the release film is not particularly limited as long as the granules for electrode containing an electrode active material can be formed on the release film and then peeled off. For example, a release agent formed on a long sheet based on PET can be used.
[0036] (B) In the case where the step of placing the granules on the surface of a release film, pressing the granules, peeling them off from the release film, and placing them on a solid electrolyte layer is included, the pressing method is not particularly limited as long as it can once form the electrode granules containing the electrode active material on the release film, but a roll-type pressure molding method is preferred. In the roll-type pressure molding method, a long PET film is pulled out from a rolled up body and is arranged so that the PET film passes between a pair of rolls before being wound up. The granules are supplied onto the PET film before passing through the rolls, and are compressed when passing between the rolls to form an electrode sheet. In order to adjust the supply amount of the granules, it is preferable to supply the thickness of the granules with a squeegee roll or the like before supplying them between the rolls.
[0037] <Battery> The battery according to this embodiment includes the above-mentioned electrode. The battery according to this embodiment can be produced according to the above-mentioned electrode embodiment or a known method.
[0038] The battery according to this embodiment may include an electrolyte layer.
[0039] The electrolyte used in the electrolyte layer includes known lithium salts and may be selected according to the type of electrode active material. The electrolyte may be, for example, LiPF6, LiBF6, LiFSI, LiClO4, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, and lithium lower fatty acid carboxylates.
[0040] The solvent for dissolving the electrolyte used in the electrolyte layer is not particularly limited as long as it is used as a liquid component for dissolving the electrolyte. The solvent may be carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), vinylene carbonate (VC), etc.; lactones such as γ-butyrolactone, γ-valerolactone, etc.; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, etc.; sulfoxides such as dimethyl sulfoxide, etc.; 1,3-dioxolane, The compound includes one or more selected from the group consisting of oxolanes such as 4-methyl-1,3-dioxolane; nitrogen-containing compounds such as acetonitrile, nitromethane, formamide, and dimethylformamide; organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and ethyl propionate; phosphate triesters and diglymes; triglymes; sulfolanes such as sulfolane and methyl sulfolane; oxazolidinones such as 3-methyl-2-oxazolidinone; and sultones such as 1,3-propane sultone, 1,4-butane sultone, and naphtha sultone.
[0041] The electrolyte layer may include a separator, and examples of the separator include a porous separator. Examples of the separator include a membrane, a film, and a nonwoven fabric. Examples of the porous separator include a polyolefin-based porous separator such as a polypropylene-based or polyethylene-based porous separator; a porous separator formed of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, or a polyvinylidene fluoride-hexafluoropropylene copolymer; and the like.
[0042] The separator may contain inorganic particles such as ceramic particles, or may further contain a layer containing inorganic particles.
[0043] The electrolyte used in the electrolyte layer may be a solid electrolyte. As the solid electrolyte, the above-mentioned solid electrolytes can be used.
[0044] Since the conductive assistant is a particle or fibrous substance with a diameter of several nm, such as carbon black or carbon nanotubes, even if it is highly dispersed in a solvent, the possibility of re-aggregation increases when a new dispersion medium is added, but in the case of an all-solid-state battery using a solid electrolyte, since it contains almost no other solvent, the present invention can be applied. When a sulfide-based solid electrolyte is used, a good battery can be obtained by manufacturing the solid electrolyte in an environment that does not contain moisture, for example, in an environment where the dew point is controlled.
[0045] The electrodes contained in the battery according to this embodiment may be in the form of, for example, a laminate or a wound body.
[0046] The shape of the battery according to this embodiment may be, for example, a square type, a cylindrical type, a coin type, a button type, or a pouch type whose case is mainly made of an aluminum film.
[0047] The method for manufacturing a battery according to this embodiment includes the method for manufacturing the electrodes described above.
[0048] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Furthermore, the present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES
[0049] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0050] <Production of positive electrodes> (Examples 1 to 9 and Comparative Example 1) A dispersion solution of the conductive assistant was prepared by highly dispersing carbon black (acetylene black) or carbon nanotubes as the conductive assistant, polyvinylpyrrolidone (PVP) as the polymer acting as the binder, in n-methylpyrrolidone as the solvent. The amount of the conductive assistant was set to the value shown in Table 1. Next, while stirring the nickel-manganese-cobalt composite oxide, which is the positive electrode active material particles, the dispersion solution of the conductive additive prepared by the above procedure was sprayed into the mixer, so that the conductive additive was attached to the surface of the positive electrode active material particles in a dispersed state without being aggregated into lumps. Next, the active material particles with the conductive additive attached thereto were placed in an agitation granulator, and the agitation blades and chopper were rotated at a specified rotation speed to spray a specified amount of the dispersion solution of the conductive additive prepared by the above procedure while mixing it with the conductive additive and the active material particles and stirring, thereby obtaining granules with the particle size shown in Table 1. The nickel-manganese-cobalt composite oxide was manufactured by MTI, and the mass ratio of nickel to manganese to cobalt was 8:1:1. Acetylene black is manufactured by Denka. PVP is manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Next, a predetermined amount of the obtained granules was supplied onto a current collector that was being wound from the unwinding side of the electrode coater to the winding side while the surface was smoothed with a squeegee. The amount of the granules supplied was adjusted via a squeegee roll at a position before the current collector passed between a pair of press rolls, and a compressed positive electrode was obtained by passing the granules through the press rolls. The density of the obtained positive electrode was 3.5 g / cm 3 It was. The volume resistivity (unit: Ω cm) was calculated by measuring the electrical resistance of the obtained positive electrode with a constant thickness and area. The results are shown in Table 1.
[0051] Comparative Example 2 A dispersion solution of the positive electrode active material particles, the conductive assistant, and the binder was prepared, the positive electrode active material particles were put into an agitation granulator, and the dispersion solution was sprayed in a predetermined amount at a time while the agitation blade and chopper were rotated at a predetermined rotation speed to obtain a granule of the conductive assistant and the active material particles. The positive electrode active material particles, the conductive assistant, and the binder were the same as those in Example 1. The obtained granules were pressed in the same manner as in Example 1 to give a density of 3.5 g / cm 3 A positive electrode of 1000 nm was obtained.
[0052] Example 10 A dispersion solution of the conductive additive was prepared by highly dispersing acetylene black as a conductive additive and polyvinylidene fluoride (PVdF) as a polymer acting as a binder in dehydrated xylene. Next, while stirring the nickel-manganese-cobalt composite oxide (positive electrode active material particles) and the Li7PS6 (solid electrolyte), the dispersion solution of the conductive additive prepared by the above procedure was sprayed into the mixer, thereby attaching the conductive additive to the surface of the positive electrode active material particles in a dispersed state without agglomerating into lumps. Next, the positive electrode active material particles with the conductive additive attached and the solid electrolyte were placed in an agitation granulator, and the agitation blades and chopper were rotated at a predetermined rotation speed to mix the conductive additive, the positive electrode active material particles, and the solid electrolyte while spraying a predetermined amount of the dispersion solution of the conductive additive prepared by the above procedure, and the conductive additive, the positive electrode active material particles, and the solid electrolyte were mixed and stirred to obtain a granule. Next, a predetermined amount of the obtained granules was supplied via a squeegee roll onto a current collector foil that was being wound from the unwinding side of the electrode coater to the winding side. The amount of the granules supplied was adjusted via the squeegee roll at a position before the current collector passed between a pair of press rolls, and a compressed positive electrode was obtained by passing the granules through the press rolls. At this time, the density of the positive electrode after pressing was 3.5 g / cm. 3 The pressure of the rolls was adjusted so that the surface and cross section of the obtained positive electrode were observed, and no aggregation of the conductive assistant was observed.
[0053] <Particle size of granules> The average particle size of the prepared granules was determined as the particle size at 50% cumulative value (median size: D50) in the particle size distribution (volume basis) by the laser diffraction scattering method. The results are shown in Table 1.
[0054] <Scanning electron microscope observation> (Presence or absence of conductive additive inside granules) The cross section of the active material layer in the electrode was observed using a scanning electron microscope at a magnification of 5000 times. Five granules were randomly selected from the images obtained by scanning electron microscope observation under the above conditions, and the presence or absence of conductive additive inside each of the five selected granules was confirmed. If the presence of conductive additive was observed inside the granules in all five granules, it was judged as "present," and otherwise it was judged as "absent." The results are shown in Table 1.
[0055] (Presence or absence of clumps of conductive additive) Five granules were randomly selected from the images obtained by scanning electron microscope observation under the above conditions, and the presence or absence of clumpy aggregates was confirmed for each of the five selected granules according to the following [Criteria for determining clumpy aggregates]. If no clumpy aggregates were observed in any of the five granules, they were marked as "absent," and otherwise "present." The results are shown in Table 1. [Criteria for determining clumps] The agglomerated portions of the conductive assistant were measured in any two directions perpendicular to each other, and when both directions exceeded 0.1 μm, the agglomerated portions were determined to be clumpy agglomerates.
[0056] <Battery manufacturing> A slurry containing graphite (negative active material), a conductive additive, a polymer called styrene-butadiene copolymer rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener was applied to a copper foil (negative current collector) as a counter electrode to the positive electrode, and pressed to a density of 1.6 g / cm. 3 The graphite used was from Nippon Graphite Industries Co., Ltd. The negative electrodes and the previously obtained positive electrodes were stacked in 10 layers with polyolefin-based porous separators between them, and negative electrode terminals electrically connected to each negative electrode and positive electrode terminals electrically connected to each positive electrode were provided to obtain a laminate. Next, an electrolyte solution prepared by dissolving LiPF6 as an electrolyte in a mixed solvent of ethylene carbonate and diethyl carbonate (ethylene carbonate:diethyl carbonate = 3:7 (volume ratio)) to a concentration of 1.0 mol / L was placed in a container with a flexible film case together with the obtained laminate, and the container was sealed with the positive and negative terminals extended to the outside to obtain a battery.
[0057] <Battery capacity retention rate after 300 cycles> The battery was placed in a thermostatic chamber at 45°C and charged at 30 mA. After the upper limit voltage reached 4.2 V, it was charged at a constant voltage until the total charging time was 2.5 hours. It was then discharged at a constant current of 30 mA until the lower limit voltage reached 2.5 V. This charge / discharge cycle was repeated 300 times, and the ratio of the 300th discharge capacity to the first discharge capacity was taken as the capacity retention rate of the battery after 300 cycles. The results are shown in Table 1.
[0058] [Table 1]
[0059] In Table 1, CB stands for carbon black and CNT stands for carbon nanotubes.
[0060] According to the embodiments of the present invention, even if the electrode granules have a large particle size of 15 μm or more, the conductive assistant is disposed inside and outside the granules in a dispersed state without agglomerating into lumps, and therefore, an electrode and a battery having low volume resistance and good cycle characteristics can be obtained.
[0061] The method described in this embodiment is merely an example and is not limited to this.
Claims
1. An electrode including a granule, The granules contain active material particles and a conductive assistant, The electrode, wherein the conductive assistant adheres to the surfaces of the active material particles in a dispersed state without agglomerating into lumps, and the conductive assistant is present inside the granules.
2. 2. The electrode according to claim 1, wherein the average particle size of the granules calculated from a scanning electron microscope photograph is 15 μm or more and 80 μm or less.
3. 3. The electrode according to claim 1, wherein the active material particles have an average particle size of 1.0 μm or more and 10.0 μm or less.
4. The electrode according to any one of claims 1 to 3, wherein the conductive assistant comprises at least one selected from the group consisting of carbon black, carbon nanofibers, and carbon nanotubes.
5. The electrode according to any one of claims 1 to 4, wherein the granules further contain a solid electrolyte.
6. A method for producing an electrode according to any one of claims 1 to 5, comprising the steps of: a step of spraying a dispersion liquid in which the conductive assistant is dispersed onto the active material particles while mixing and stirring the active material particles to form the granules; placing the granules on a current collector and pressing them; A method for producing an electrode comprising the steps of:
7. A method for producing the electrode according to claim 6, comprising the steps of: a step of mixing and stirring the active material particles and the solid electrolyte, while spraying and adding the dispersion liquid in which the conductive assistant is dispersed to the active material particles to form the granules; (A) a step of placing the granules on a surface of a current collector or a surface layer formed on the surface of a current collector and pressing the granules, or (B) a step of placing the granules on a surface of a release film, pressing the granules, peeling them off from the release film, and placing the granules on a solid electrolyte layer; A method for producing an electrode comprising the steps of:
8. A battery comprising the electrode according to any one of claims 1 to 5.
9. 9. The battery of claim 8, The battery further includes an electrolyte layer.
10. A method for producing a battery, comprising the method for producing an electrode according to claim 6 or 7.
Citation Information
Patent Citations
Composite material for positive electrode of lithium battery
JP2009176721A
Manufacturing method of electrode sheet
JP2015201318A